1405. High risk or unstable substance use may predict OPAT nonadherence among people who use drugs (PWUD) admitted with invasive infections. (15th December 2022) - Ching, Patrick R; George, Nivya; Kottilil, Shyam; Narayanan, Shivakumar
Abstract: Background: Patients with substance use disorder (SUD) are frequently admitted to hospitals for invasive infections and may have poor infection outcomes including non-adherence and lack of completion of therapy. Methods: In this retrospective cohort of 263 hospital encounters among 201 patients for invasive infections due to SUD to an urban tertiary care facility, we looked at characteristics of SUD to assess whether there were differences in infections, their management, SUD interventions and parenteral antibiotic outcomes between groups. Results: Among people with SUD, 79% of antibiotic courses were completed in skilled nursing facilities. Most common infectious syndromes were osteoarticular infections (123, 47%), infective endocarditis (IE) (54, 20%) and non-IE endovascular infection (23, 9%). Among SUD specific interventions, 64% of episodes had documentation of a consultation by substance use services and 68% episodes had documentation of medication for opioid use disorder (MOUD) being prescribed at discharge. Overall, completion of therapy was documented in 163 (62%) of encounters. Overall, treatment non-adherence was seen in 63 encounters (24%). Non-adherence was documented 32% of episodes with documentation of injection drug use (IDU), 28% of encounters where active substance use was documented in the prior year and 33% of encounters where use of more than one substance was documented (P< 0.05 for all 3 groups). Drug or catheter related adverse events seemed to be significantly higher in the IDU group (3.64/1000 OPAT days) and catheter abuse was documented in 7 encounters of which 6 were with IDU or active SUD active documented. Cumulatively an unfavorable outcome (including failure, 30-day readmission, drug or PICC related adverse event, non-adherence or death) seemed to occur in 58% of IDU encounters as compared to non-IDU encounters (42.5%, P=0.011). Medication for opioid use disorder (MOUD) was prescribed at discharge in 68% of overall cohort and was not associated with improved outcomes for any of the above groups. Demographics, infection details and outcomes by type of SUD Conclusion: In patients hospitalized with SUD-related infections, interventions need to be focused on those with high risk, unstable SUD through MOUD optimization along transitions of care and linkage to care to improve OPAT outcomes and overall health events Disclosures: Shyam Kottilil, MD, PhD, Arbutus Pharmaceuticals: Grant/Research Support|Gilead: Grant/Research Support|Merck: Grant/Research Support|Regeneron Pharmaceuticals: Advisor/Consultant|Silverback Therapeutics: Advisor/Consultant|The Liver Company: Advisor/Consultant|Yufan Biotechnologies: Advisor/Consultant.